Community participation in health, a public health challenge - Marisa Morales Loyola (Social Medicine Publication Group, 2022)
Within the inherent activities of the State, the development of services that seek to satisfy the needs of citizens is a continuous process, since it depends on it that individuals manage to carry out their daily activities without serious problems, as well as ensure their well- being. Therefore, the relationship between the government and society must move from governability to governance, which is based on three dimensions: democracy, development and rights16, and implies the active participation of the population in order to generate and build co-responsibility and achieve changes.